Loading-unloading behavior of a clayey rock under thermo-hydro-mechanical conditions. (December 2021) - Yu, Hongdan; Chen, Weizhong; Gong, Zhe; Tan, Xianjun; Yang, Diansen
Abstract: Various investigations have been carried out on the hydro-mechanical behavior of geomaterials, but those of clayey rock are still limited. Among these existing studies, very few data are available related to the thermal effects, particularly the loading-unloading behavior of clayey rock at high temperatures. In this paper, undrained loading-unloading triaxial tests on undisturbed specimens of Boom Clay extracted from Mol, Belgium, were carried out with the aim to study (1) the influence of temperature and load path on the thermo-hydro-mechanical behavior of clayey rock, and (2) the formation mechanism of loading-unloading stress-strain hysteresis loops. The test results first revealed the stress paths–dependent stress-strain behavior of Boom Clay. The increase of initial mean effective stress p 0 ′ has a positive effect on the mechanical behavior of Boom Clay. Secondly, temperature elevation induced the strength weakening of Boom Clay even under loading-unloading conditions. Thirdly, the p 0 ′ and temperature had a bearing on the loading-unloading elastic modulus (defined as the peak-to-peak secant modulus of a hysteresis loop). Strain energy dissipation during the loading-unloading is then discussed from the perspective of thermodynamics. Finally, the study concludes that the stress-strain hysteresis loops for Boom Clay may be closely related to its high content of adsorbed water, and it may be driven by the combined effect of "friction resistance" and "viscous resistance."